2009
DOI: 10.4037/ajcc2009353
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care Units, Communication Between Nurses and Physicians, and Patients’ Outcomes

Abstract: Background Various factors in hospitals can adversely affect patients' outcomes, including faulty communication between nurses and physicians. Whether specific communication elements (timeliness, accuracy, openness, understanding) can influence adverse outcomes is unknown. Objectives To determine the relationships between patients' outcomes and (1) nurses' perceptions of elements of communication between nurses and physicians and (2) characteristics of the practice environment. Methods A cross-sectional survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 41 publications
1
66
1
2
Order By: Relevance
“…단순 관계를 살펴보거나, 간호사의 소진과 업무성과와의 관계 등을 다룬 선행연구들이었다 (Happ et al, 2011;Manojlovich et al, 2009;Melzer & Huckabay, 2004;Shimizu et al, 2003).…”
Section: 현재까지 국외의 경우 중환자실 간호사들을 대상으로 의사 소통 능력 소진 또는 간호업무성과 의 개념을 다룬 unclassified
“…단순 관계를 살펴보거나, 간호사의 소진과 업무성과와의 관계 등을 다룬 선행연구들이었다 (Happ et al, 2011;Manojlovich et al, 2009;Melzer & Huckabay, 2004;Shimizu et al, 2003).…”
Section: 현재까지 국외의 경우 중환자실 간호사들을 대상으로 의사 소통 능력 소진 또는 간호업무성과 의 개념을 다룬 unclassified
“…[11][12][13] Results of earlier studies link workplace empowerment with characteristics of professional nursing practice such as higher levels of job satisfaction, 14,15 communication, 13 and an enhanced patient safety climate. 16 Because workplace empowerment has been associated with positive characteristics of professional nursing, it is not surprising that a recent study showed a higher perceived level of empowerment in certified nurses than in noncertified nurses (P < .008).…”
Section: Nursing Specialty Certification and Workplace Empowermentmentioning
confidence: 99%
“…14 The study by Piazza and colleagues 10 was based in the United States and had a mean total empowerment score of 21.28; that study included staff nurses and nurses at all levels of position (including managers and advanced practice nurses) in a small community hospital. In a recent study 16 among critical care nurses from 25 intensive care units, Manojlovich and colleagues studied perceptions of empowerment as related to communication between nurses and physicians and selected patient outcomes.…”
Section: Intend To Leavementioning
confidence: 99%